Warriors of God : Richard the Lionheart and Saladin in the Third Crusade - Reston, James Jr. 1941- (London Faber and Fabber, 2001)
The story of the Third Crusade, and the two men who dictated its outcome: Saladin, hero of the Islamic world, and Richard the Lionheart. Richard and the King of France led a European army of several hundred thousand warriors, but Saladin's manoeuvres resulted in the crusaders' retreat.
Include Biliography and Index
Keywords: Crusades -- Crusades (Third : 1189-1192) -- Saladin, Sultan of Egypt and Syria, 1137-1193